Loving-Kindness Meditation to Target Affect in Mood Disorders: A Proof-of-Concept Study. (1st June 2015) - Hofmann, Stefan G.; Petrocchi, Nicola; Steinberg, James; Lin, Muyu; Arimitsu, Kohki; Kind, Shelley; Mendes, Adriana; Stangier, Ulrich
Abstract : Conventional treatments for mood disorders primarily focus on reducing negative affect, but little on enhancing positive affect. Loving-kindness meditation (LKM) is a traditional meditation practice directly oriented toward enhancing unconditional and positive emotional states of kindness towards oneself and others. We report here two independent and uncontrolled studies carried out at different centers, one in Boston, USA (n = 10), and one in Frankfurt, Germany (n = 8), to examine the potential therapeutic utility of a brief LKM group intervention for symptoms of dysthymia and depression. Results at both centers suggest that LKM was associated with large-sized effects on self-reported symptoms of depression (d = 3.33 and 1.90), negative affect (d = 1.98 and 0.92), and positive affect ( d = 1.63 and 0.94). Large effects were also found for clinician-reported changes in depression, rumination and specific positive emotions, and moderate effects for changes in adaptive emotion regulation strategies. The qualitative data analyses provide additional support for the potential clinical utility of the intervention. This proof-of-concept evaluation of LKM as a clinical strategy warrants further investigation.